Modelo van hiele como estrategia lúdica para la enseñanza aprendizaje de la geometría básica en los estudiantes de sexto año de educación general básica paralelo “A” en la unidad educativa Ángel Polibio Chávez, periodo 2023-2024. - Agualongo Chimbolema, Edgar Jhoel (2024)
The present research was developed with the purpose of applying the Van Hiele model as a playful strategy for the teaching- learning of basic geometry in sixth year students of parallel Basic General Education "A" of the Ángel Polibio Chávez Educational Unit, since They fail to understand the teaching strategies taught by their teachers, the results of which are reflected in poor academic performance; Therefore, students have difficulty understanding the area of mathematics, specifically in the subject of geometry. The methodology has a mixed qualitative-quantitative approach, whose research design was descriptive and bibliographic with inductive and inductive methods. In addition, a survey and an interview were used as research techniques, which were applied to 30 sixth-year students of Education. Basic, where all the information was processed through the Excel statistical program. The results of the research showed the difficulties presented by the students with respect to the learning of basic geometry, likewise, it was found that the didactic resources currently used are not the most adequate for the teaching- learning process, which made it necessary to apply the Van Hiele model as a didactic strategy, concluding that this model allowed improving the learning of geometry, which was found through the levels of reasoning and the phases that the theory of learning and teaching of geometry possesses.